Optimizing biology learning outcomes: Uncovering the impact of the student project-based learning model - Yuliandari; Aminuddin Prahatama Putra; Yudi Firmanul Arifin (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2024)
Project-Based Learning (PjBL) is a learning model that actively engages students in educational activities, particularly those emphasizing creativity aimed at developing both products and conceptual understanding. This approach focuses on designing and implementing projects to solve problems while enhancing students' learning outcomes. The purpose of this study is to explore the impact of project-based biology learning (PjBL) on students' academic performance. The research method involves analyzing data sourced from Google Scholar over the past five years. A number of relevant articles were identified and used as reference materials, with 10 articles selected for further analysis. These articles were examined based on the skills developed and their influence on students' learning outcomes in project-based biology education. The findings from the review of these articles conclude that the PjBL model has a positive impact on improving students' academic performance in both high schools and vocational education institutions. Abstrak. Project Based Learning (PjBL) merupakan model dalam pembelajaran yang melibatkan peserta didik dalam kegiatan pembelajaran khususnya yang berkaitan dengan suatu kreatifitas yang berorientasi pada perolehan produk dan konsep baik dalam merancang maupun membuat proyek yang bertujuan untuk pemecahan masalah dan peningkatan hasil belajar pesertaa didik dalam pembelajaran. Tujuan dalam penelitian ini untuk mengungkapkan dampak pembelajaran biologi berbasis proyek (PjBL) terhadap hasil belajar peserta didik. Metode penelitian ini menggunakan analisis  hasil pencarian dari data Google Scholar dengan rentang waktu 5 tahun terakhir. Berdasarkan hasil pencarian diperoleh banyak artikel relevan yang dipergunakan sebagai bahan studi rujukan dalam penelitian. 10 jumlah artikel di data, kemudian dianalisis berdasarkan kemampuan yang dikembangkan dari hasil penelitian pada hasil belajar peserta didik dalam pembelajaran biologi berbasis proyek. Hasil dari analisis telaah dalam review artikel dapat disimpulkan bahwa temuan model pembelajaran PjBL berdampak baik untuk meninkatkan hasil belajar peserta didik baik pada satuan pendidikan di SMA maupun SMK.